2017
DOI: 10.1002/adfm.201700992
|View full text |Cite
|
Sign up to set email alerts
|

“Tissue Papers” from Organ‐Specific Decellularized Extracellular Matrices

Abstract: Using an innovative, tissue-independent approach to decellularized tissue processing and biomaterial fabrication, the development of a series of “tissue papers” derived from native porcine tissues/organs (heart, kidney, liver, muscle), native bovine tissue/organ (ovary and uterus), and purified bovine Achilles tendon collagen as a control from decellularized extracellular matrix particle ink suspensions cast into molds is described. Each tissue paper type has distinct microstructural characteristics as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 75 publications
2
62
0
1
Order By: Relevance
“…Grover et al used PEG‐acrylate materials to modulate mechanical properties of cECM scaffolds, and showed that fibroblast viability was not hindered by polymer inclusion . Jakus et al used a variety of dECM materials, including cECM, to create thin, large “tissue papers” for use in patching applications via the incorporation of poly‐lactic‐ co ‐glycolic acid (PLGA) . The cECM‐derived paper showed effective MSC proliferation, although the technology was not evaluated further in the study.…”
Section: Soluble Decmmentioning
confidence: 99%
“…Grover et al used PEG‐acrylate materials to modulate mechanical properties of cECM scaffolds, and showed that fibroblast viability was not hindered by polymer inclusion . Jakus et al used a variety of dECM materials, including cECM, to create thin, large “tissue papers” for use in patching applications via the incorporation of poly‐lactic‐ co ‐glycolic acid (PLGA) . The cECM‐derived paper showed effective MSC proliferation, although the technology was not evaluated further in the study.…”
Section: Soluble Decmmentioning
confidence: 99%
“…Recently, bovine ovaries have been decellularized using detergent-based methods to obtain a tissue-specific scaffold, which was re-seeded with healthy follicles and transplanted to restore cycling in an ovariectomized mouse 67 . Similarly, porcine and bovine decellularized ovaries were further processed into "tissue papers", demonstrating a versatile approach for short-term in vitro culture of nonhuman primate and human ovarian cortical strips 68 . Although acellular ovarian scaffolds have been shown to support follicle function in this form, they are limited by the quantity of follicles that can be seeded and require additional time for in vitro culture to allow follicles to attach.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this scaffold has diverse physiological functions such as being a reservoir of cytokines and GFs, transmitting specific signals through interactions with the receptors of the cell surface, and providing natural circumstances to regulate the phenotype, attachment, migration and proliferation of cells . Recently, several kinds of acellular scaffolds have been successfully developed for tissue‐engineering . Unfortunately, the acellular scaffolds derived from dense tissue is low in porosity, and thus not convenient for cell infiltration, partly limiting their usage .…”
Section: Discussionmentioning
confidence: 99%